The implication of the Paris targets for the Middle East through different cooperation options - Mohammad M. Khabbazan; Christian von Hirschhausen (Energy Economics, 2021)
The core of the 36th round of the Energy Modeling Forum project shows that it is more likely that major fossil-fuel exporters, such as the Middle East, are highly affected because of the decrease in fossil-fuel extractions required for the worldwide fulfillment of the Paris agreement. We employ a multi-region, multi-sector computable general equilibrium model of global trade and energy to examine the effects of implementing the Paris agreement with a focus on the Middle East which is further disaggregated into Iran, Saudi Arabia, the rest of net fossil fuel exporting countries (XFE), and the rest of countries (XNE). After examining the abatement costs for the regions, we apply four emission reduction targets, ranging from a low ambition level to a high ambition level. We develop comprehensive scenarios covering several cooperation options within the Middle East and between the Middle East and selected regions outside. The results show that Iran has the lowest marginal abatement cost in the Middle East, followed by XNE, XFE, and Saudi Arabia. If the Middle East does not implement any climate policy, the welfare losses can be slightly compensated due to a carbon leakage to the Middle East. The cooperations within the Middle East are not welfare increasing for the region as a whole when Iran mainly benefits from such cooperation whereas Saudi Arabia loses welfare. The Middle East benefits from global cooperation and the cooperation with Europe, but the cooperation with China, India, or Russia can be welfare decreasing.
Keywords: C68; F13; F18; Q58; 330; Climate mitigation; Computable general equilibrium; Emissions trading; Middle East; Regional cooperation